RISK MANAGEMENT OF INDUSTRIAL RADIOGRAPHY PERSONNEL CERTIFICATION ACTIVITIES TO ENSURE WORKER SAFETY AND HEALTH - Ratih Luhuring Tyas; Farah Nurfuadia; Alfitri Meliana (Jurnal Forum Nuklir, 2020)
RISK MANAGEMENT of Industrial Radiography Personnel Certification Activities to Ensure Worker Safety and Health. The increasing use of radioactive substances and other radiation sources in the Indonesian industry for non-destructive testing lead to a rise in the need for radiographers. In carrying out certification activities, NQSC utilizes radioactive sources in the form of gamma rays from X-ray appliances. Therefore adequate risk management to ensure the safety and health of participants is needed. The risk management process carried out by PSMN uses the hierarchy principle at ISO 45001 and other preventive measures regulated in the IAEA Safety Guidelines, with the measures evaluated periodically using dose reading data. The dosage results on workers and examinees showed that the dose value is below the allowable value with a Dose Limit Value (NBD) of no more than 20 mSv per year. This means that the risk management measures guarantee worker safety and health in the certification activities of industrial radiography personnel in PSMN.